Periocular keratoacanthoma: can we always rely on the clinical diagnosis?. Issue 9 (19th August 2005) - Leibovitch, I; Huilgol, S C; James, C L; Hsuan, J D; Davis, G; Selva, D
Abstract : Aim: To present a series of patients with a clinical diagnosis of periocular keratoacanthoma and assess the incidence of histologically proven invasive squamous cell carcinoma (SCC). Methods: This retrospective case series included all patients with periocular tumours seen in the authors' unit between 1996 and 2004, and who were initially diagnosed with keratoacanthoma based on the clinical presentation. Results: Twelve patients (eight males, four females) were clinically diagnosed with keratoacanthoma. The final histological diagnosis revealed two cases (16.7%) of invasive SCC, and 10 cases (83.3%) of keratoacanthoma. The lower lid was most commonly involved in cases of keratoacanthoma (50.0%). Six patients (60.0%) underwent Mohs surgery, and four (40.0%) were treated with excision under frozen section control. There were no cases of recurrence during a mean follow up period of 21 (SD 13) months. Conclusion: Although the clinical presentation of periocular keratoacanthoma is usually characteristic, a significant percentage of patients will prove to have invasive SCC. Complete excision with margin control offers a definitive diagnosis, as well as tissue conservation and a low recurrence rate.